1998
DOI: 10.1093/clinchem/44.3.599
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter evaluation of the Paragon CZETM 2000 capillary zone electrophoresis system for serum protein electrophoresis and monoclonal component typing

Abstract: Serum protein electrophoresis and typing of monoclonal components (MCs) are routine but time-consuming and technically demanding assays. We evaluated capillary electrophoresis (Paragon CZETM 2000) for automation of the two assays. CZE and cellulose acetate electrophoresis gave similar data on 794 samples. Within-run and between-run CVs were <2% for albumin and γ-globulins and 4–7% for α1-, α2-, and β-globulins. Bilirubin, hemoglobin, triglycerides, and fibrinogen were found not to interfere. No carryove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…Although Dutch guidelines 3 recommend a detection limit of 0.5--1g/L, Table 1. several authors 1,2,4 have indicated that M protein concentrations below 5 g/L are hard to identify by CZE/IS. By selecting a random panel of participants and by composing our plots (samples) so as to represent the most common immunotypes at low concentrations, we tried to obtain a representative impression of the average detection limits achieved by trained participants when detecting and identifying low concentrations of M proteins by CZE/IS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Dutch guidelines 3 recommend a detection limit of 0.5--1g/L, Table 1. several authors 1,2,4 have indicated that M protein concentrations below 5 g/L are hard to identify by CZE/IS. By selecting a random panel of participants and by composing our plots (samples) so as to represent the most common immunotypes at low concentrations, we tried to obtain a representative impression of the average detection limits achieved by trained participants when detecting and identifying low concentrations of M proteins by CZE/IS.…”
Section: Resultsmentioning
confidence: 99%
“…Capillary zone electrophoresis/immunosubtraction (CZE/IS) is an automated method for immunotyping monoclonal components (M proteins) in serum. Despite its good analytical quality and wide availability, 1 CZE/IS is not applied frequently in Dutch clinical hospital laboratories. CZE/IS patterns have been found to be particularly di⁄cult to interpret in the case of a high polyclonal immunoglobulin background or co-migration of the M protein with other peaks, especially at low concentrations (o5 g/L).…”
Section: Introductionmentioning
confidence: 99%
“…We therefore established reference values for CZE analysis in a Japanese population 8) , but the clinical application of those values to pathological serum was not assessed. Thus, the aim of the present study was to investigate whether the electrophoretic patterns and clinical information derived from the five principal fractions of Paragon CZE 2000 agree with the results of CAE, since the findings in previous reports [2][3][4][5] were derived from non-Japanese adults.…”
Section: Introductionmentioning
confidence: 87%
“…Serum protein fractionation by cellulose acetate electrophoresis (CAE) is used to diagnose a variety of disorders 1) , but paraprotein spikes can be identified much more precisely by capillary zone electrophoresis (CZE) in combination with an immunosubtraction procedure (Beckman Paragon CZE 2000 system) [2][3][4][5] . In Japan, evaluations of the Paragon CZE 2000 system have been reported by Sakurabayashi 6) specifically in regard to M-proteins and an α 1 -globulin fraction that poorly bound dyes, and by our laboratory in regard to minor components (e.g., prealbumin, α 1 -acid glycoprotein, α 1 -antitrypsin, hemopexin, transferrin, and complement) together with the principal five fractions 7,8) .…”
Section: Introductionmentioning
confidence: 99%
“…These are detected and measured by monitoring absorbance at 214 nm. 1 Results are presented in traditional electrophoretic fractions-albumin, α1, α2, β, and γ fractions-as percentages of total protein detected. A total protein value, which is measured by Biuret on Abbott Aeroset, is then used in the CZE system to calculate the concentrations of the fractions, including monoclonal bands (in g/litre).…”
mentioning
confidence: 99%